Frequency of middle mesial canals in mandibular first and second molar using cone beam computed tomography in Hyderabad - Kheem Chand; Feroze Ali Kalhoro; Madiha; Shuja Aslam; Sarang Suresh; Priya Rani (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: There is still a lack of comprehensive research on the demographic characteristics that contribute to these differences, particularly age and gender. To determine the frequency and type of Middle Mesial Canal (MMC) in permanent mandibular first and second molars using CBCT.METHODOLOGY: The inclusion criteria consisted of individuals of any gender, aged 18 to 60 years, who had first or second mandibular permanent molars referred by the Department of Diagnosis due to unsuccessful endodontic therapy. Analyzed in a systematic manner, CBCT images were used to assess the intricacy of the root canal anatomy in the first and second mandibular molars in all three planes. The middle mesial canal (MMC) was identified and documented according to the classification established by Pomeranz.RESULTS: In relation to the presence of middle mesial canals (MMC) in first molars, a small proportion (1.4%) exhibit MMC that are either connected to the mesiobuccal canal, separate from the mesiobuccal canal, or connected to the mesiolingual canal.CONCLUSION: The presence of MMC in the first molars was rather rare, as the majority (95.8%) of the sample did not show this anatomical variation. No MMCs were observed in second molars in this study.